Acute Pain Management for Patients with Substance Use Disorder Receiving Buprenorphine or Methadone Compared to Patients without Opioid-Dependence Disorder. (17th March 2022) - Vogler, Carrie; Arnold, Stephen; Surbeck, Erin; Conklen, Katelyn; Deshpande, Maithili
Abstract: This single-center retrospective study assessed pain management between patients being treated for SUD and compared them to those without SUD who underwent orthopedic surgery. Patients with SUD could be admitted for any reason, while the control arm consisted of patients undergoing total knee arthroplasty or hip arthroplasty surgery. Primary endpoints were average pains scores and morphine milligram equivalents (MME) over the first 48h. Secondary endpoints include adjuvant pain medications and the average MME prescribed upon discharge. A total of the 60 patients were enrolled, 30 patients had history of SUD and 30 patients in the control arm. Average MME between the SUD and control was not significantly different (139.9 mg vs. 96.6 mg, p = 0.889). Average pain scores between the groups were significantly different (7.46 vs. 5.94, p = 0.002). Patients with SUD were not given a statistically different amount of MME for acute pain and experienced higher pain scores than patients without SUD. However, this study had a small population size, and further case–control studies are needed to confirm this result.